Model HOT-FIT dalam Menilai Keberhasilan Implementasi Aplikasi Gemini serta Dampaknya pada Kepuasan Pengguna - Dewi Lusiana; Aji Brahma Nugroho (Puslitbang Sinergis Asa Professional, 2026)
The rapid development of Artificial Intelligence (AI) has increased the use of the Gemini application to support information retrieval, task completion, and work productivity. This study aims to analyze the factors influencing the successful use of the Gemini application using the Human-Organization-Technology Fit (HOT-FIT) model. The variables examined include Service Quality, User Satisfaction, Organizational Structure, and Net Benefit. A quantitative approach with purposive sampling was employed. Data were collected from 100 respondents, consisting of students, lecturers, and employees, and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results indicate that all constructs meet the validity and reliability requirements. The R-Square values of 0,588 for User Satisfaction and 0,676 for Net Benefit demonstrate satisfactory explanatory power. Hypothesis testing shows that Service Quality has a positive and significant effect on User Satisfaction (β=0.767; p<0.001), User Satisfaction has a positive and significant effect on Net Benefit (β=0.274; p=0.023), and Organizational Structure has a positive and significant effect on Net Benefit (β=0.599; p<0.001). These findings indicate that the HOT-FIT model effectively explains the success of the Gemini application, highlighting the importance of service quality and organizational support in maximizing its benefits.